Considerações Gerais Sobre Epidemiologia do Câncer no Brasil - Marsillac, Jorge de (2023)
Report presented to the VII International Cancer Congress held in July, 1958, at London. The authors, Dr. Jorge de Marsillac, chief of the Organization and Control Department of The National Cancer Service; and Professor Achilles Scorzelli Jr. Director of the Public Health School, make several remarks about Cancer Epidemiology in Brazil, particularly in Rio de Janeiro, during the period from 1952 to 1956. They arrive to the same conclusions previously mentioned by others that while a country develops, mortality by infecious diseases decreases and mortality degenerative ones increases. They point the difficulties of an statistical survey even only of mortality. Considering that the non-determined death causes coefficient even in Brazilian main cities, and these difficulties grow extraordinarily in the in interland where there is a great number of regions without a single doctor. The author also emphasize the statistical findings of Cancer National Institute, at Rio de Janeiro, during the same period and point to some cancer localisation, out of rate, and to the reasons that, under their opinions, would be responsible for them.